Establishment of human trabecular meshwork cell cultures using nontransplantable corneoscleral rims - WADUTHANTHRI, Kosala D. (Turk J Biol, 2019)
Human trabecular meshwork (hTM) cell isolation in academic settings utilizes the motile nature of these cells, allowing them to migrate away from the explant and proliferate on distal regions of the culture substrate. Corneoscleral rims used for transplantation are a potential source of explants for the establishment of hTM cell cultures. However, cell isolation and the initiation of primary cell cultures from ocular tissues stored in Optisol-GS medium for an extended period of time (>6 days) has proven difficult, since Optisol-GS remarkably reduces cell viability and cellularity. Therefore, explants obtained from ocular tissues stored in Optisol-GS do not often provide adequate cell yield to initiate primary cell cultures if conventional culture techniques are used. Therefore, the majority of the research on primary hTM cell isolation has been accomplished using donor tissue obtained within 72 h postmortem. The goal of this study was to develop an hTM cell isolation procedure from nontransplantable ocular materials, utilizing the anchorage dependency of TM cells. This procedure yielded functionally viable cells, eficiently dissociated from the trabecular meshwork. Isolated cells demonstrated typical hTM cell characteristics including monolayer formation, contact inhibition, phagocytosis, and responses to glucocorticoid exposure. To the best of our knowledge, this is the first time an expired explant has been utilized in the successful isolation of hTM cells. Our results clearly demonstrate the advantage of increasing the anchor points of hTM cells for enhanced cell migration out from the explants, which have limited cell proliferative capacity.